1983
DOI: 10.4038/jnsfsr.v11i2.8387
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the hygienic quality of market foods in Kandy

Abstract: A total of 183 samples of consumable items of food and drink exposed for sale in the Kandy Municipal area were subjected to bacteriological examination with regard t o its hygienic quality. Only 19 per cent of the samples of ice cream examined were within the limits of the bacteriological standards laid down by the Sri Lanka Bureau of Standards. Other desserts (Fruit salad, Woodapple cream) show lower mean bacterial densities (Escherichia coli I, faecal streptococci and total viable count) than ice cream. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many studies showed a compatible results and reported that more than 40% of the ice cream samples (n=50), were contaminated with E. coli (10,16,17).…”
Section: Discussionmentioning
confidence: 91%
“…Many studies showed a compatible results and reported that more than 40% of the ice cream samples (n=50), were contaminated with E. coli (10,16,17).…”
Section: Discussionmentioning
confidence: 91%
“…Acorus calami L, Cedrus deodar, Coriandrum sativam, Clerondendron serratum, Fumariya parviflora, Munronia pumila, Myrica esculenta, Chlorocyperus salaamensis, Terminaliya chebuala, Zingiber officinale, are composed of the decoction. As per the Sloka, It alleviates the diseases of Kapha and Vāta origin of fever, hiccup, Svāsa (relieves breathing difficulties) and Gala Roga (throat diseases), Kāsa (relieves cough), Sosha (desiccation), Hanu Rōga (disease of temporal region) [13,14] . The current study was based on a critical review regarding COVID-19 through Ayurveda perspective to address effective management protocol for the condition referring Dasa Panguwa decoction.…”
Section: Introductionmentioning
confidence: 99%